PENGARUH LITERASI KEUANGAN, PERILAKU KEUANGAN, PENDAPATAN, DAN MASA KERJA TERHADAP KEPUTUSAN INVESTASI (Studi pada Karyawan PT Hwaseung Indonesia) - Irfana, Naila; Wibowo, Purwo Adi (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
An investment decision refers to an investor's strategy in selecting or determining where to allocate their investment capital to optimize potential future returns. Various factors can influence such decisions, including financial literacy, economic behavior, income levels, and length of service. Testing the impact of individual financial literacy, individual financial behavior, income level, and tenure on employee investment choices at PT Hwaseung Indonesia is the aim of this research. Data for this research were collected through a purposive sampling technique by giving surveys to PT Hwaseung employees via Google Forms. The analysis was conducted using SPSS software version 26, employing multiple linear regression methods. The findings reveal that financial literacy, income, and tenure have a positive and statistically significant impact on investment decisions. Conversely, financial behavior does not exhibit a significant relationship with investment decision.